Struktur Komunitas Plankton di Danau Pondok Lapan Desa Naman Jahe Kecamatan Salapian Kabupaten Langkat (Structure Community Plankton in Pondok Lapan Lakedesa Naman Jahe Kecamatan Salapian Kabupaten Langkat) - Fahmi Fadhli Rais; Yunasfi Djayus; Ahmad Muhtadi (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
In aquatic ecosystems, plankton is a big role in the food chain. This is because therole of plankton as producers (phytoplankton) and first level consumer (zooplankton) in thewaters for other organisms that it can be used as a feeding including fish. This research isfocused on plankton for structure community and measurement of physical and chemicalfactors. This research was held in January-March 2015. The method of research is by usingpurposive random sampling to determine the station's for some intent and purpose. Thecarrying out of plankton did by using Van Dorn water sampler a modified water samplingand then filtered with a plankton net no. 25. The diversity of plankton in these watersclassified as the medium category with H '2.121 value. The types of plankton which found inhigh abundance is Scenedesmus, Chodatella and Ankistrodesmus. And from the types ofzooplankton are Cyclops, Branchionus and Nauplius. Based on its saprobic coefficient isknown that these waters classified as moderately polluted by 1,158 value and classified intothe phase of βmeso/oligosaprobik.Keywords : Pondok Lapan Lake, Structure Community, Plankton, Saprobik.